The Unsolvability of Inverse Algebraic Eigenvalue Problems Almost Everywhere (Journal of Computational Mathematics, 2018)
This paper revises the definition for the unsolvability of inverse algebraic eigenvalue problems almost everywhere (a.e.) given by Shapiro [5], and gives some sufficient and necessary conditions such that the inverse algebraic eigenvalue problems are unsolvable a.e.